2017
DOI: 10.11118/actaun201765010225
|View full text |Cite
|
Sign up to set email alerts
|

Barn Owl (Tyto alba) Diet Composition on Intensively Used Agricultural Land in the Danube Lowland

Abstract: Based on pellets analysis from five localities in south western Slovakia (Malá Mužla, Malé Ripňany, Obid, Opatovský Sokolec and Tešedíkovo), we studied the diet composition of Barn Owl (Tyto alba) in intensively cultivated agricultural lands. A total of 6218 specimens of prey, 17 mammalian and 7 bird species were identified. The main prey species found in all food samples was the Common Vole (Microtus arvalis), varying between 56 % and 67 %. The proportion of synanthropic species (Rattus norvegicus, Passer dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Our results are in accordance with other studies conducted in Europe (e.g. Milchev 2015, Veselovský et al 2017, in South-America (Leveau et al 2006, Gonzalez-Fischer et al 2011, Teta et al 2012, and in North-America (Marti et al 1988(Marti et al , 2010 which reported that the dominance of small mammals, particularly the high frequency of an available and profitable prey in the diet, explained the low values of niche breadth. Our results confirmed that the food niche breadth of Barn Owls was significantly higher in an urban landscape, caused by the decrease of predominant Microtus voles as main prey items (Hindmarch & Elliott 2015) and by the increase of commensal rodents (rats, house mice) as alternative prey which are associated with human activities (Salvati et al 2002, Teta et al 2012, Hindmarch & Elliott 2015.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in accordance with other studies conducted in Europe (e.g. Milchev 2015, Veselovský et al 2017, in South-America (Leveau et al 2006, Gonzalez-Fischer et al 2011, Teta et al 2012, and in North-America (Marti et al 1988(Marti et al , 2010 which reported that the dominance of small mammals, particularly the high frequency of an available and profitable prey in the diet, explained the low values of niche breadth. Our results confirmed that the food niche breadth of Barn Owls was significantly higher in an urban landscape, caused by the decrease of predominant Microtus voles as main prey items (Hindmarch & Elliott 2015) and by the increase of commensal rodents (rats, house mice) as alternative prey which are associated with human activities (Salvati et al 2002, Teta et al 2012, Hindmarch & Elliott 2015.…”
Section: Discussionsupporting
confidence: 93%
“…According to our results the greatest proportion of Striped Field Mouse in pellet samples of urban land reflected the relatedness of this species with urban and suburban habitat patches. We found that the Common Vole was the most abundant prey in each of the landscape types considered, the same predominance having been reported by other studies in central Europe (Goszczyński 1977, Horváth et al 2005, Kitowski 2013, Petrovici et al 2013, Purger 2014, Veselovský et al 2017. Despite this general predominance, the significant heterogeneity of overall proportion values proved that the consumption frequency of common voles was higher in the agricultural than in the urban landscape.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The food consumption of the Common Barn-owl is mainly determined by changes in the density of agricultural pest rodents such as different Microtus vole species, both in temperate zones of Nearctic and Paleartic regions and the Mediterranean (Colvin & MacLean 1986, Marti 1988, Taylor 1994, Shehab & Al Charabi 2006, Charter et al 2009, Kitowski 2013, Petrovici et al 2013, Purger 2014, Veselovský et al 2017. Due to their preference and high rates of consumption, several studies demonstrated negative correlation between vole (Microtus spp.)…”
Section: Introductionmentioning
confidence: 99%